Study of pregnancy induced hypertension in relation to placental and fetal birth weight - Gupta, Deepti; Khan, Shabana; Noor, Nazia; Bhargava, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: A healthy placenta is the most important factor in producing a healthy baby. Placenta which is the most important organ for maintaining and continuing healthy pregnancy and fetal growth. Study aimed to evaluate Pregnancy induced hypertension in relation to placental and fetal birth weight. Methods: Total 200 mothers participated in the study, various parameters related with placental and fetal weight were calculated and analysed. Results: This study observed the reduction of placental weight in the hypertensive disorders. Placental weight shows marked variation in all the groups and coefficient of variation was higher in severe PIH group, but mean weight was less with increased severity of PIH. Baby weight shows marked variation in all the groups and coefficient of variation was increased with severity of PIH and mean weight was less with increased severity of PIH. Placental weight was significantly reduced in pre-eclamptic pregnancies and it was directly correlated with fetal birth weight. Conclusions: Hypertensive disorders of pregnancy adversely influence the placental weight, which ultimately, adversely influence the maternal and perinatal outcomes.